Importance of cone beam computed tomography in the diagnosis of root perforation: a case report (Research, Society and Development, 2021)
Endodontic perforations are defined as a iatrogenic mechanical communication between the root canal and supporting periodontal tissues. Dental imaging techniques are essential for satisfactory detection of these conditions. The purpose of this study was to describe the clinical case of a patient diagnosed with endo-periodontal cystic lesion by endodontic perforation by cone beam computed tomography (CBCT). A 67-year-old female patient who required oral rehabilitation treatment with an implant-supported denture in the posterior mandible was seen at the Dental Clinic of the State University of Rio Grande do Norte (UERN). Based on the data collected during clinical examination, complementary tests were requested for assessment of his overall dental condition. Periapical radiography revealed the presence of a lesion in the apex of tooth 22, which was associated with an endodontic lesion. CBCT showed a lateral lesion caused by root perforation suffered during prior endodontic treatment. After histopathological analysis, the diagnosis was a radicular cyst. This study highlights the importance of CBCT imaging for establishment of the correct diagnosis, treatment planning, and prevention of complications.